Learn ECG in a day : a systematic approach - Sajjan M.; Maben, EVS (Panamá : Jaypee-Highlights, 2013)
Interpretation of electrocardiograph is an essential part of cardiovascular diangnosis. ECG is an important diagnostic tool in the diagnosis of cardiac as well as some metabolic problems. To read an ECG correctly, one has to be thorough with the basic knowledge of electromechanical system of the heart. It also requires a lot of imaginations and logic conclusions.
La interpretación del electrocardiógrafo es una parte esencial de la diangnosis cardiovascular. El ECG es una importante herramienta de diagnóstico en el diagnóstico de problemas cardíacos y metabólicos. Para leer un ECG correctamente, uno tiene que ser exhaustivo con los conocimientos básicos del sistema electromecánico del corazón. También requiere mucha imaginación y conclusiones lógicas.
CONTENTS 1. HISTORY OF ECG 2. PHYSIOLOGY OF CONDUCTION SYSTEM OF HEART 3. BASICS OF ECG 4. ECG LEADS 5. PLACEMENT OF LEADS AND OTHERS MORE...
Incluye índice
Incluye bibliografía
Keywords: ELECTROCARDIOGRAFÍA; ENFERMEDADES DE CORAZÓN -- DIAGNÓSTICO; ARRHYTHMIA